Sociocultural Analysis of Millennials in Russia - E. V. Zaburdaeva (Концепт: философия, религия, культура, 2020)
The article provides a sociocultural analysis of parameters of the millennials, the generation which will become the basic workforce in Russia in the next 10 years. It being topical, the major attention of the paper is dedicated to market and micro-interactionist influence of basic traits of millennials. The issue of treating millennials is faced both sociologically and managerially. It is said that the large number of conflicts between millennials and older generations leads to systematic inconvenience and turbulence, as it does not allow young employees to integrate in corporate cultures and increase own labor efficiency, at the same time affecting older employees, the management and corporative performance. Another aspect of the core issue raised by the author is educating the youth. Understanding the set of core values of millennials, their strategies and tactics of behavior in the workplace also becomes a prerequisite for teachers to successfully train students of this generation in universities. This research, in addition to many recent ones, examines that millennials can be characterized with such distinctive features. They, being digital natives, shift to more rapid, discrete and depersonalized forms of communication. Focused on managing their personal image and identity, millennials prefer playing socially desirable roles and tend to reframe own failures into external misfortunes. This brings about the issue of meeting the set goals, and nowadays the youth tends to plan less and rather get more usual feedback which is expected to be positive. These features are most likely to breed intergeneration misunderstanding. However, what is surely discovered to be helpful in settling controversies is that millennials tend to be more flexible and tolerant than other generations, which tells on general success of interaction and effort. The author, addressing the challenges of communication with modern youth, offers recommendations based on his own pedagogical experience of interaction with millennials. These are: provide basic guidelines and time plans as well as assessment benchmarks. Managerial staff should also dedicate more effort to mentorship and peer-level communication.